Grit Instrument Development on High School Students: Rasch Model Analysis - Ahmad Yudiar; Mamat Supriatna; Eka Sakti Yudha (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aimed to develop an instrument that will be used to measure the grit of senior high school students. This quantitative study involved 601 senior high school students in Bangka Belitung. Based on an analysis of the relevant literature, this study developed 24 items that collectively described grit. Data was collected using a grit scale and analyzed using the Rasch model. The results show that 1) Cronbach's alpha value is 0.91 which means the interaction between item and person is in the very good category, 2) the item reliability coefficient is 0.97 where the item belongs to the special category, and 3) the person reliability coefficient is 0.87 which means that students respond consistently to each item. Based on the results above, we can see that 23 valid items and the other is invalid. Overall, it can be concluded that the grit scale has good psychometric properties, and it can be used by counselors or counseling guidance teachers to measure students' grit.